(3GdfXGe GdbGfhfj dYbO GdGMJQGa GdQjGVj (B/ s - (3YHO Gddg EeMeO Nda GdWQGhfgs; (3LYaQ GdeZQHj s; (3SYjO SdjeGf LHQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2013)
(3bO CVMi ef GdeYdhe Cf YbO GdGMJQGa GdQjGVj GdPj jHQeg GddGYH GdeMJQa eY GdfGOj GdLOjO HYO fhYG ef CfhGY YbhO GdYed, aGddGYH jCNP CLkQG jYJeO Ydjg aj eUOQ QRbg h eYjTJg, ebGHd LgOg GdPj jHPdg eY GdfGOj GdefJej Edjg, CKfGA eTGQcJg aj GdeHGQjGJ hGdeSGHbGJ hGdHWhdGJ GdJj jTJQc ajgG GdfGOj GdQjGVj, hjchf GddGYH NGVYG dETQGa hQbGHI GdfGOj JMJ EWGQ GdeSFhdjI GdJCOjHjI(B. (3ceG Efg ddGJMGO GdQjGVj GdeMdj Md GdefGRYGJ GdJj bO JfTC eG Hjf GddGYHjf GdeMJQajf hGdCfOjI GdQjGVjI Ydi GdeSJhi GdeMdj, HSHH JfajP HfhO GdYbO Ch dGFMI GdGMJQGa hJaSjQ HfhOgeG(B. (3hEf GdbQGQGJ GdUGOQI Yf dLfI aV GdefGRYGJ jWYf HgG CeGe LgI eNJUI JSei dLfI GdGSJFfGa, haj GdfgGjI Je GdJhUd Edi LedI ef GdfJGFL hGdJhUjGJ CgegG(B: (3Je hVY ebJQM dgjcd JfXjej dgjFI JMcje QjGVjI, hef Ke Je hVY ebJQM JYdjeGJ GdEMJQGa GdQjGVj dcd ef eUQ hGdCQOf hhVY JYOjdGJ hfUhU ebJQMI aj bGfhf GddLfI GdChdeHjI GdCQOfj hGdeUQjI, hfXGe GdGJMGOGJ GdQjGVjI GdCQOfj hGdeUQjs
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdeOfj (B2013.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B460-495.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3YbhO GdQjGVIs; (3YbO GdGMJQGa GdQjGVjs; (3eOfjI YbO GdGfJbGd GdQjGVj ef JLGQJgs; (3GfbVGA YbO GdGMJQGa GdQjGVjs; (3GdfGOj GdQjGVj s; (3GddGYH GdQjGVj GdeMJQas; (3JShjI GdefGRYGJ GdQjGVjIs; (3BdjI JShjI GdefGRYGJ GdQjGVjI GdOhdjIs; (3eMceI GdJMcje GdQjGVj GdOhdjs; (3NUhUjI YbO GdYGed GdeMJQas; (3GfbVGA YbO GdYGed GdeMJQas; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs